High pressure treatment of green mussel Perna viridis Linnaeus, 1758: effect on shucking and quality changes in meat during chill storage - Bindu, J.; Ginson, J.; Kamalakanth, C. K.; Gopal, T. K. S. (Indian Journal of Fisheries, 2015)
Effect of high pressure on shucking of mussel meat from shell and quality changes in meat in terms of pH, total volatile base nitrogen (TVBN), thiobarbituric acid value (TBA), instrumental colour values (lightness, L*; redness, a* and yellowness, b*), instrumental hardness, total plate count (TPC) and sensory analysis during chill storage were evaluated. Shell-on mussels were pressure treated at 100, 200, 300 and 400 MPa with a holding time of 5 min at 30±3°C. The pressure treated meat was then aseptically removed from the shell and vacuum packed in laminated pouches made of polyester low density polythene and stored at 2±1°C for shelf life evaluation. Manually shucked mussel meat not subjected to pressure treatment served as control. pH and TBA values increased with increasing pressure treatment. Instrumental colour values (L*, a* and b*) and hardness were more for mussel meat subjected to 400 MPa pressure treatment. After high pressure treatment, TVBN and TPC decreased compared to control, however, these values increased during storage. Among the treated samples, 300 MPa shucked mussel meat was sensorially superior to others and had a shelf life of 28 days during chill storage (2±1°C).